2016
DOI: 10.1016/j.jmb.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Death Receptor 5 Networks Require Membrane Cholesterol for Proper Structure and Function

Abstract: Death receptor 5 (DR5) is an apoptosis-inducing member of the tumor necrosis factor receptor superfamily, whose activity has been linked to membrane cholesterol content. Upon ligand binding, DR5 forms large clusters within the plasma membrane that have often been assumed to be manifestations of receptor co-localization in cholesterol-rich membrane domains. However, we have recently shown that DR5 clusters are more than just randomly aggregated receptors. Instead, these are highly structured networks held toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 86 publications
(91 reference statements)
1
25
0
Order By: Relevance
“…Results by Song et al showed that TRAIL-induced activation of DR5, measured by activation of Caspase-8, is sensitive to the presence of cholesterol in the membrane [116]. Our recent results demonstrate that plasma membrane physical and biochemical properties facilitate DR5 dimer formation [85]. We first showed in cells that DR5 agonists induce migration of the receptor to cholesterol-rich membrane regions, and depletion of membrane cholesterol using methyl-β-cyclodextrin (MβCD) reduces ligand-induced activity.…”
Section: From the Ectodomain To The Cytosol Via The Transmembrane mentioning
confidence: 89%
See 4 more Smart Citations
“…Results by Song et al showed that TRAIL-induced activation of DR5, measured by activation of Caspase-8, is sensitive to the presence of cholesterol in the membrane [116]. Our recent results demonstrate that plasma membrane physical and biochemical properties facilitate DR5 dimer formation [85]. We first showed in cells that DR5 agonists induce migration of the receptor to cholesterol-rich membrane regions, and depletion of membrane cholesterol using methyl-β-cyclodextrin (MβCD) reduces ligand-induced activity.…”
Section: From the Ectodomain To The Cytosol Via The Transmembrane mentioning
confidence: 89%
“…In the case of TNFR1, structures demonstrate pre-ligand dimerization via the PLAD [73], however other experiments suggest pre-ligand trimerization [76]. Despite the early focus on the PLAD, we and others have recently demonstrated a clear role for the TM domain and intracellular contacts in dimerization and activity of TNFRs [3,8385]. However, whether these non-PLAD interactions are conserved and how essential they are among all TNFRs remains to be seen.…”
Section: Crystal Structures Of Isolated Soluble Domains Offer An Amentioning
confidence: 99%
See 3 more Smart Citations